Ácido giberélico na superação da dormência em sementes de ravenala - Silva, Josiane Carvalho Fonseca (2020)
Ravenala (Ravenala madagascariensis), also known as the traveler’s tree, is a tropical plant species commonly used for garden ornamentation. Since the seeds of this tree present dormancy and slow development, the tree is more vegetatively propagated by division and replanting of clumps. Thus, the objective of this study was to evaluate the effect of gibberellic acid (GA3) on breaking the dormancy of ravenala seeds in order to develop an efficient in vitro germination protocol and to optimize the ex vitro germination process. The seeds were initially immersed for 15, 30 and 45 minutes in 2.5% sodium hypochlorite (NaOCL). The effect of GA3 on breaking seed dormancy was analyzed both by applying acid to the culture medium and by applying it during the process of seed imbibition. Ravenala seeds were scarified in sulfuric acid for 10 minutes and then they were inoculated in MS medium supplemented with 0, 10, 20, 40 or 80 μM of GA3. For the imbibition process, after scarification in sulfuric acid for 10 minutes, the seeds were imbibed in solution with different GA3 concentrations (0, 250, 500, 750, and 1000 mg L-1). After 24 and 48 hours the seeds were inoculated in MS medium for in vitro germination or they were placed in tubes containing commercial substrate Tropstrato® and Vermiculite for ex vitro germination. Hydrogen peroxide (H2O2), lipid peroxidation, as well as α-amylase activities of embedded seeds were also determined. Our result showed that seeds were successfully disinfested after 15 minutes immersed in NaOCL. The culture medium supplemented with 20 μM of GA3 promoted the higher percentage germination (95%) compared with the other tested concentrations. The GA3 also provided significant results for other plant growth parameters. Seed imbibition for 24 or 48 hours promoted an in vitro germination average of 80%. However, there was no significant difference on germination percentage between seeds embedded in solution with or without GA3. In extra vitro germination the seed imbibition in solution with 250 mg L-1 and 1000 mg L-1 of GA3 promoted the higher germination percentage (25%) in 24 and 48h respectively. Therefore, according to our results the use of culture medium supplemented with 20 μM of GA3 and seed imbibition for 24 to 48 hours regardless the use of GA3 is recommended to break the dormancy of ravenala seeds and to optimize the in vitro germination.